STUNTING IS NOT GENDER-NEUTRAL: A LITERATURE REVIEW - Rahmawati, Maulida; Putri, Nuzulul Kusuma (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
Background: Stunting is one of the undernutrition outcomes commonly reported in LMICs. It results from chronic or recurrent undernutrition and is associated with social determinants. Indonesia has promoted various programs to reduce and prevent stunting. The programs tend to not be gender-responsive with no existence of gender analysis on the programs. Purpose: To analyze the intersectionality of gender with other social determinants of stunting, transforming into any stunting program barriers within the health system. Methods: This narrative review was conducted using original research articles on the Scopus database. Two independent reviewers performed review selection and characterization. We grouped the identified gender intersectionality and constraints imposed on stunting programs based on three-levels of health systems. Results: There were 19 papers included in this literature review. Two main messages were identified. First, gender has a different impact on any health program. It interacted with other social determinants in shaping the risk of being stunted. Second, the gender intersectionality will be different for each level of health system. Conclusion: Gender intersects with different social determinants in each level of the health system. The impact of gender intersectionality with other stunting determinant stunting is identified. Hence, stunting is not gender neutral.